2022
DOI: 10.15376/biores.18.1.1206-1214
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glue-free zones on the withdrawal capacity of glued-in steel threaded rods

Abstract: The hidden nature of a glued-in rod joint presents considerable challenges with regards to quality control, and there has been minimal research on the subject to fully understand the influence of defects on the joint performance. In this study, voids in adhesive line or glue-free zones were simulated in various depths of the embedded rod, and the results were compared to a reference sample population without defects. Withdrawal capacity of glued-in steel threaded rods were lower compared to reference group sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The results revealed that employment status was the only sociodemographic factor that had a significant effect on the aesthetic preference of the respondents. This finding is consistent with some previous studies that have found employment status to be a predictor of aesthetic preference [61,62]. This finding is interesting, as it suggests that employment status may be related to other factors, such as income, lifestyle, values, or exposure to design, that may affect the aesthetic judgment and preference of consumers [10,53].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results revealed that employment status was the only sociodemographic factor that had a significant effect on the aesthetic preference of the respondents. This finding is consistent with some previous studies that have found employment status to be a predictor of aesthetic preference [61,62]. This finding is interesting, as it suggests that employment status may be related to other factors, such as income, lifestyle, values, or exposure to design, that may affect the aesthetic judgment and preference of consumers [10,53].…”
Section: Discussionsupporting
confidence: 91%
“…Traditional timber joints, such as mortise and tenon joints, have a rich history in Asian countries, preserving the original beauty and aesthetics of timber without relying on steel fasteners [61]. However, advancements in fasteners and joint design have revolutionised timber construction, enabling the efficient construction of largescale structures with enhanced durability and performance [62]. The behaviour of timber joints is intricately linked not only to the load-carrying capacity of individual fasteners but also to their form and interaction within the joint itself [63].…”
Section: Timber Jointsmentioning
confidence: 99%